2019
DOI: 10.1016/j.cjca.2019.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction in Severe Mental Illness: Prevalence, Clinical Outcomes, and Process of Care in U.S. Hospitalizations

Abstract: Background: Severe mental illness (SMI) is associated with increased cardiovascular mortality. We sought to examine the prevalence, clinical outcomes and management strategy of patients with SMI presenting with acute myocardial infarction (AMI). Methods: All AMI hospitalizations from the National Inpatient Sample were included, stratified by mental health status in to 5 groups: no-SMI, Schizophrenia, 'Other non-organic psychoses' (ONOP), Bipolar Disorder and Major Depression. Regression analyses were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 43 publications
2
18
1
1
Order By: Relevance
“…These rates were also lower among women across all study groups. 4 These findings align with previously published work from the NIS, which showed a persistent gap in revascularization in patients with SMI (particularly schizophrenia) despite the increasing use of percutaneous revascularization over time. 7 authors to study an often-overlooked subgroup of patients who are rarely recruited into clinical trials.…”
Section: Clinical Outcomes and Management Of Acute Myocardial Infarction In Patients With Smisupporting
confidence: 90%
See 3 more Smart Citations
“…These rates were also lower among women across all study groups. 4 These findings align with previously published work from the NIS, which showed a persistent gap in revascularization in patients with SMI (particularly schizophrenia) despite the increasing use of percutaneous revascularization over time. 7 authors to study an often-overlooked subgroup of patients who are rarely recruited into clinical trials.…”
Section: Clinical Outcomes and Management Of Acute Myocardial Infarction In Patients With Smisupporting
confidence: 90%
“…[5][6][7] Most studies have investigated SMI subtypes of schizophrenia and bipolar disorder; however, the current study by Mohamed et al expanded on the previous literature by including additional diagnoses (especially major depression) within SMI and further stratifying according to sex. 4 Significantly, the highest rates of inhospital mortality were observed in men and women with schizophrenia. This troubling finding concurs with multiple previous studies in various cohorts, including the NIS.…”
Section: Clinical Outcomes and Management Of Acute Myocardial Infarction In Patients With Smimentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to that, pre-existing mental health affects post MI recovery as these patients are less likely to receive interventions. In the United States between 2004 and 2014 Mohamed et al 4 found that in 6,968,777 acute myocardial infarction hospitalisations, 439,544 patients (6.5%) had a severe mental illness diagnosis. The rates of reported depression increased throughout this period with 3.4% reporting depression in 2004 to 8.1% in 2014.…”
Section: And Qudsia Mehwishmentioning
confidence: 99%